Makna Kandoushi pada serial animasi Isshukan Friend - Silvia Rahmadhani Yafas; Hendri Zalman (Omiyage : Jurnal Bahasa dan Pembelajaran Bahasa Jepang, 2022)
This research is motivated by the difficulty of understanding the kandou meaning contained in a conversation so that it can lead to misundertsandings in interpreting the meaning that the speaker wants to convey. The objectives of this study were to   the meaning of kandoushi kandou contained ini the animated series Isshukan Friend. The purpose of this research is to find out what kandoushi kandou are contained ini the animated series Isshukan Friend and to know the meaning contained there in. This research is a qualitative research with descriptive methods. The data ini this study are words or sentences which contain kandoushi kandou spoken by characters ini the animated series Isshukan Friend. The instrument in this study was the researcher himself. In this research, 13 data on kandoushi kandou were found. Kandoushi kandou which were found, namely; 1) ee means to express a feeling of surprise, 2) maa means to express a feeling amazed, 3) are means to express a feeling of weird and surprise, 4) hora means to  express a feeling of surprise and pressure, 5) aa means to express a feeling of  regret, and 6) hee means to express a feeling of surprise.